2001
DOI: 10.1074/jbc.m100083200
|View full text |Cite
|
Sign up to set email alerts
|

Classes of Thiols That Influence the Activity of the Skeletal Muscle Calcium Release Channel

Abstract: The skeletal muscle Ca 2؉ release channel/ryanodine receptor (RyR1) is a prototypic redox-responsive ion channel. Nearly half of the 101 cysteines per RyR1 subunit are kept in a reduced (free thiol) state under conditions comparable with resting muscle. Here we assessed the effects of physiological determinants of cellular redox state (oxygen tension, reduced (GSH) or oxidized (GSSG) glutathione, and NO/O 2 . (released by 3-morpholinosydnonimine)) on RyR1 redox state and activity. Oxidation of ϳ10 RyR1 thiols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
133
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 38 publications
4
133
0
3
Order By: Relevance
“…Moreover, endogenous NO production inside muscle fibers serves an important function as an antioxidant by directly scavenging oxygen radicals and by modifying the influence of oxygen radicals on excitation-contraction coupling. Indeed, NO modulates the activity of sarcoplasmic reticulum ryanodine receptors and Ca 2ϩ release through S-nitrosylation of critical cystein residues (25). NO also protects these receptors from the deleterious effects of oxygen radicals that elicit disulfide bond formation of critical cystein residues (24).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, endogenous NO production inside muscle fibers serves an important function as an antioxidant by directly scavenging oxygen radicals and by modifying the influence of oxygen radicals on excitation-contraction coupling. Indeed, NO modulates the activity of sarcoplasmic reticulum ryanodine receptors and Ca 2ϩ release through S-nitrosylation of critical cystein residues (25). NO also protects these receptors from the deleterious effects of oxygen radicals that elicit disulfide bond formation of critical cystein residues (24).…”
Section: Discussionmentioning
confidence: 99%
“…The RyR1 of SR membrane possesses several highly reactive sulfhydryl (SH) groups that are susceptible to oxidation (Sun et al 2001). Abramson and Salama (1989) reported that oxidised SH groups can stimulate calcium release by forming disulfide bonds, which cause the RyR1 to maintain in the open state.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Chaque sous-unité compte entre 38 et 48 thiols à l'état libre, sensibles à l'oxydation. L'état d'activation de RYR1 répond de manière biphasique à l'administration de doses croissantes d'oxydants, le maximum d'activation se situant pour un état impliquant 23 SH/RYR1 [2]. L'oxyde nitrique NO est également considéré comme un modulateur physiologique de l'état redox de RYR1 par S-nitrosylation [3].…”
Section: Régulation Redox De Ryr1unclassified
“…Cependant les mécanismes exacts impliqués dans ce processus inflammatoire restent mal connus. Dans deux revues récentes, les équipes de Randal Kaufman et Laurie Glimcher ont décrit le rôle potentiel des voies de signalisation du stress émanant du réticulum endoplasmique (RE) dans l'inflammation et la réponse immunitaire [1,2]. Cette réponse cellulaire intégrée -appelée Unfolded Protein Response (UPR) -est activée en réponse à une accumulation de protéines mal conformées dans la lumière du RE.…”
Section: Inflammation Intestinale Et Stress Du Réticulum Endoplasmiquunclassified